Effect of Student Knowledge About Earthquake Disaster on Preparedness in Middle School - Merthaguna, Anak Agung Rai Sandhi; Nasution, Nasution; Jacky, Jacky (International Journal for Educational and Vocational Studies, 2020)
This study aims to analyze the effect of students' knowledge about the earthquake disaster on preparedness at Dampelas 6 Middle School. The method used is quantitative with a type of explanatory research. The research variables consist of independent variables, namely knowledge about earthquake disasters, while the dependent variable is readiness. The research sample used was 56 respondents obtained using the proportional sampling technique with the Taro Yamane method. Data collection techniques using questionnaires and tests. Data analysis uses a simple linear regression test. The results showed that statistically simple linear regression with Î± = 5% (2-sided test, 0.05: 2 = 0.025) and degrees of freedom (n-2-1) or 56-2-1 = 53 obtained t table of 2.005, knowledge variable (X1) with readiness (Y) students about earthquake disaster obtained t-count 3.392, while t-table 2.005, then Ho is rejected and Ha is accepted, which means that partially student knowledge has a significant influence on earthquake disaster preparedness ( 3,392> 2,005). Based on the results of a simple regression test, it was concluded that students' knowledge of the earthquake disaster-affected preparedness at Dampelas 6 Middle School by 3.392.